Combination of Silicate-Based Soil Conditioners with Plant Growth-Promoting Microorganisms to Improve Drought Stress Resilience in Potato - Abdullah Al Mamun; Günter Neumann; Narges Moradtalab; Aneesh Ahmed; Fahim Nawaz; Timotheus Tenbohlen; Jingyu Feng; Yongbin Zhang; Xiaochan Xie; Li Zhifang; Uwe Ludewig; Klára Bradáčová; et al. (Microorganisms)
Due to shallow root systems, potato is a particularly drought-sensitive crop. To counteract these limitations, the application of plant growth-promoting microorganisms (PGPMs) is discussed as a strategy to improve nutrient acquisition and biotic and abiotic stress resilience. However, initial root colonization by PGPMs, in particular, can be affected by stress factors that negatively impact root growth and activity or the survival of PGPMs in the rhizosphere. In this study, perspectives for the use of commercial silicate-based soil conditioners (SCs) supposed to improve soil water retention were investigated. The SC products were based on combinations with lignocellulose polysaccharides (Sanoplant® = SP) or polyacrylate (Geohumus® = GH). It was hypothesized that SC applications would support beneficial plant–inoculant interactions (arbuscular mycorrhiza, AM: Rhizophagus irregularis MUCL41833, and Pseudomonas brassicacearum 3Re2-7) on a silty loam soil–sand mixture under water-deficit conditions (6–12 weeks at 15–20% substrate water-holding capacity, WHC). Although no significant SC effects on WHC and total plant biomass were detectable, the SC-inoculant combinations increased the proportion of leaf biomass not affected by drought stress symptoms (chlorosis, necrosis) by 66% (SP) and 91% (GH). Accordingly, osmotic adjustment (proline, glycine betaine accumulation) and ROS detoxification (ascorbate peroxidase, total antioxidants) were increased. This was associated with elevated levels of phytohormones involved in stress adaptations (abscisic, jasmonic, salicylic acids, IAA) and reduced ROS (H2O2) accumulation in the leaf tissue. In contrast to GH, the SP treatments additionally stimulated AM root colonization. Finally, the SP-inoculant combination significantly increased tuber biomass (82%) under well-watered conditions, and a similar trend was observed under drought stress, reaching 81% of the well-watered control. The P status was sufficient for all treatments, and no treatment differences were observed for stress-protective nutrients, such as Zn, Mn, or Si. By contrast, GH treatments had negative effects on tuber biomass, associated with excess accumulation of Mn and Fe in the leaf tissue close to toxicity levels. The findings suggest that inoculation with the PGPMs in combination with SC products (SP) can promote physiological stress adaptations and AM colonization to improve potato tuber yield, independent of effects on soil water retention. However, this does not apply to SC products in general.